Penerapan Model Pembelajaran Kooperatif Tipe Team Games Tournament untuk Meningkatan Hasil Belajar Pendidikan Agama Hindu Siswa Kelas V SD Negeri 4 Karangasem - Ni Ketut Murtikawati (Jayapangus Press, 2021)
This research is motivated by the low learning outcomes of Class V students at SD Negeri 4 Karangasem in Hindu Religious Education. This is thought to be caused by several factors, the learning method used by the teacher is still monotonous, which only uses the lecture method. This classroom action research was carried out in two cycles with the aim of improving the learning outcomes of Hindu Religious Education. The subjects of this study were the fifth grade students of SD Negeri 4 Karangasem with a total of 12 students consisting of 5 female students and 7 male students. Data were collected using the test method. The collected data was then analyzed by qualitative descriptive statistics. The results of the study show that the application of the team games tournament type cooperative learning model in learning Hindu Religious Education can improve student learning outcomes, namely classically on initial reflection by 42% students complete, cycle I by 75% students complete, and cycle II by 100% students. finished. Therefore, between the initial reflection and the first cycle there was an increase in classical completeness by 33%. Meanwhile, from cycle I to cycle II there was an increase in classical completeness by 25%. Based on these results, several suggestions can be recommended, namely: the principal should seek to provide various learning resources that can support the learning activities carried out, Hindu religious education teachers are expected to continue to optimize learning activities carried out through the application of various innovative methods, especially cooperative learning models. Team Games Tournament type, so as to improve student learning outcomes, students are expected to increase their seriousness in participating in the learning process, so that learning materials can be well understood. That means the learning objectives will be achieved well too, and other researchers should participate in testing this method in learning Hindu Religious Education on different subjects from the subjects in this study.